2016
DOI: 10.1103/physrevd.93.016006
|View full text |Cite
|
Sign up to set email alerts
|

Diboson excesses in an anomaly free leptophobic left-right model

Abstract: The resonant excesses around 2 TeV reported by the ATLAS Collaboration can be explained in the left-right model, and the tight constraints from lepton plus missing energy searches can be evaded if the SU (2) R gauge symmetry is leptophobic. We for the first time propose an anomaly free leptophobic left-right model with gauge symmetry SU (3) C × SU (2) L × SU (2) R × U (1) X where the SM leptons are singlets under SU (2) R . The gauge anomalies are cancelled by introducing extra vector-like quarks. The mass of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 53 publications
(28 reference statements)
0
9
0
Order By: Relevance
“…In particular, for appropriate values of its parameters, trinification can also reproduce the eejj excess [72], as already discussed in [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] in the context of dedicated models. Needless to say, all decay widths can be computed in terms of unknown masses and of the mixing angles introduced above.…”
Section: Jhep03(2016)025mentioning
confidence: 66%
“…In particular, for appropriate values of its parameters, trinification can also reproduce the eejj excess [72], as already discussed in [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] in the context of dedicated models. Needless to say, all decay widths can be computed in terms of unknown masses and of the mixing angles introduced above.…”
Section: Jhep03(2016)025mentioning
confidence: 66%
“…Recently, the left-right scenarios have been revised [15][16][17][18][19][20][21][22][23][24][25] in order to make contact with the latest experimental data of LHC. Moreover, the dark matter problem [26][27][28] and the diphoton excess anomaly [29][30][31][32][33] have been explored in this kind of scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…The deviation has been associated to possible signatures of various beyond-the-SM models, e.g. models with new W and Z vector bosons (see for example [35][36][37][38][39][40][41][42][43][44]), models involving new resonances with different spins (see for example [45][46][47][48][49][50][51][52]), composite and technicolor models (see for example [53][54][55][56][57][58]) and new and composite Higgs states (see for example [59][60][61][62][63][64][65][66][67]). A review of the different models offering an interpretation of the deviations reported in the ATLAS and CMS searches has been made in Ref.…”
Section: Introductionmentioning
confidence: 99%